Economic evaluation of integrated services for non-communicable diseases and HIV: costs and client outcomes in rural Malawi - Luckson Dullie; Emily B Wroe; Elizabeth L Dunbar; Noel Kalanga; Lawrence Nazimera; Adarsh Shah; Bright Mailosi; Chiyembekezo Kachimanga; Ryan K McBain; Natalie Price; Mahlet Gizaw; Chantelle Boudreaux; et al. (BMJ Open)
Objective To evaluate the costs and client outcomes associated with integrating screening and treatment for non-communicable diseases (NCDs) into HIV services in a rural and remote part in southeastern Africa.Design Prospective cohort study.Setting Primary and secondary level health facilities in Neno District, Malawi.Participants New adult enrollees in Integrated Chronic Care Clinics (IC3) between July 2016 and June 2017.Main outcome measures We quantified the annualised total and per capita economic cost (US$2017) of integrated chronic care, using activity-based costing from a health system perspective. We also measured enrolment, retention and mortality over the same period. Furthermore, we measured clinical outcomes for HIV (viral load), hypertension (controlled blood pressure), diabetes (average blood glucose), asthma (asthma severity) and epilepsy (seizure frequency).Results The annualised total cost of providing integrated HIV and NCD care was $2 461 901 to provide care to 9471 enrollees, or $260 per capita. This compared with $2 138 907 for standalone HIV services received by 6541 individuals, or $327 per capita. Over the 12-month period, 1970 new clients were enrolled in IC3, with a retention rate of 80%. Among clients with HIV, 81% achieved an undetectable viral load within their first year of enrolment. Significant improvements were observed among clinical outcomes for clients enrolled with hypertension, asthma and epilepsy (p<0.05, in all instances), but not for diabetes (p>0.05).Conclusions IC3 is one of the largest examples of fully integrated HIV and NCD care. Integrating screening and treatment for chronic health conditions into Malawi’s HIV platform appears to be a financially feasible approach associated with several positive clinical outcomes.